Indoleamine 2, 3‐dioxygenase promotes peritoneal metastasis of ovarian cancer by inducing an immunosuppressive environment. Issue 8 (27th June 2014) - Tanizaki, Yuko; Kobayashi, Aya; Toujima, Saori; Shiro, Michihisa; Mizoguchi, Mika; Mabuchi, Yasushi; Yagi, Shigetaka; Minami, Sawako; Takikawa, Osamu; Ino, Kazuhiko
<x xml:space="preserve">Abstract</x> Indoleamine 2, 3‐dioxygenase (IDO) is a tryptophan‐catabolizing enzyme that has immunoregulatory functions. Our prior study showed that tumoral IDO overexpression is involved in disease progression and impaired patient survival in human ovarian cancer, although its mechanism remains unclear. The purpose of the present study is to clarify the role of IDO during the process of peritoneal dissemination of ovarian cancer. Indoleamine 2, 3‐dioxygenase cDNA was transfected into the murine ovarian carcinoma cell line OV2944‐HM‐1, establishing stable clones of IDO‐overexpressing cells (HM‐1‐IDO). Then HM‐1‐IDO or control vector‐transfected cells (HM‐1‐mock) were i.p. transplanted into syngeneic immunocompetent mice. The HM‐1‐IDO‐transplanted mice showed significantly shortened survival compared with HM‐1‐mock‐transplanted (control) mice. On days 11 and 14 following transplantation, the tumor weight of peritoneal dissemination and ascites volume were significantly increased in HM‐1‐IDO‐transplanted mice compared with those of control mice. This tumor‐progressive effect was coincident with significantly reduced numbers of CD8+ T cells and natural killer cells within tumors as well as increased levels of transforming growth factor‐β and interleukin‐10 in ascites. Finally, treatment with the IDO inhibitor 1‐methyl‐tryptophan significantly suppressed tumor dissemination and ascites with reduced transforming growth factor‐β secretion. These findings showed that tumor‐derived IDO promotes the peritoneal dissemination of ovarian cancer through suppression of tumor‐infiltrating effector T cell and natural killer cell recruitment and reciprocal enhancement of immunosuppressive cytokines in ascites, creating an immunotolerogenic environment within the peritoneal cavity. Therefore, IDO may be a promising molecular target for the therapeutic strategy of ovarian cancer.